Osteoporosis reversibility in a patient with celiac disease and primary autoimmune hypothyroidism on gluten free diet: A case report - Kovačev-Zavišić Branka; Ičin Tijana; Novaković-Paro Jovanka; Medić-Stojanoska Milica; Bajkin Ivana (Vojnosanitetski Pregled)
Introduction. Secondary osteoporosis occurs in many diseases. Celiac disease-induced osteoporosis is the consequence of secondary hyperparathyroidism. Biochemical bone markers show predominance of bone resorption, thus making the bisphosphonates the first line therapy option. Intestinal mucosal changes are reversible on gluten-free diet. Osteoporosis reversibility is also possible, provided postmenopausal osteoporosis risk factors independent from celiac disease are not present. Case report. We presented a postmenopausal woman with at least a 10-year history of celiac disease prior to diagnosis, which had overt secondary hyperparathyroidism with insufficient status of vitamin D and a significant bone mass reduction. At the time of diagnosis of celiac disease the patient was receiving 250 􀆬g of levothyroxine daily without achieving optimal substitution. Three years after the initiation of gluten-free diet the patient was without any signs and symptoms of the disease. All laboratory findings were within normal range. It was decided to treat the underlying disease and to supplement calcium and vitamin D without the initiation of bisphosponate therapy. Conclusion. Osteoporosis regression justified this therapeutic approach. The presence of primary autoimmune hypothyroidism makes this case specific, since the inability for optimal substitution therapy with a high daily dose of levothyroxine provoked the suspicion of celiac disease.